Realitas Kekerasan Seksual Berbasis Elektronik: Analisis Habitus Pierre Bourdieu Terhadap Budaya Patriarki Pelaku - Nur Alfy Syahriana; Mohammad Fauzan Ni'ami (Pusat Studi Gender dan Anak, IAIN Palu, 2024)
In the current era, patriarchal culture is able to adapt to social changes in modern society that cannot be separated from the digital space. This indicates that there is a transformation of a patriarchal culture that is publicly patriarchal in social practice. Then, whether we realize it or not, these conditions have contributed to the increase in cases of Electronic Based Sexual Violence (EBSV). This research will focus on two important things, namely uncovering the causes of the strong patriarchal culture in the digital space and analyzing the patriarchal habitus of EBSV actors. This field research takes place at WCC Dian Mutiara Malang City using a sociological approach and then analyzed with Pierre Bourdieu's habitus theory. The findings of this study indicate that there are three factors that cause strong patriarchy in EBSV actors. First, there is the transformation and crystallization of patriarchal culture in the digital space that it creates public patriarchy in modern society. Second, the current state system. Third, the performance of law enforcement officials in handling EBSV cases is not optimal. In Pierre Bourdieu's review, the patriarchal habitus of EBSV perpetrators is influenced by patriarchal values that develop in community social practices, the perpetrator's perception of the practice, and the appreciation of the perpetrator shown by carrying out EBSV against the victim.